English english - Prita Ayu Permatasari; Luisa Febrina Amalo; Rahmat Pangestu; Marfian Dwidima Putra (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Citarum River is one of the strategically valuable rivers in Indonesia, especially on Java Island. Since 2018, the central government has carried out the "Citarum Harum" program to revitalize the river while improving its reputation of Citarum as one of the dirtiest rivers in the world. This study aimed to see the pollution load capacity of the downstream Citarum River 4 years after the revitalization program was implemented. Downstream Citarum Watershed (Karawang Regency) was chosen as the focus of the study site because of the very high risk of contamination. This research was comparing the pollution load capacity of biochemical oxygen demand (BOD) in 2022 using Qual2Kw software and 2017 based on the data analyzed by the Ministry of Environment and Forestry. River revitalization over the last 4 years has significantly reduced the BOD value in the downstream Citarum Watershed. The success of this revitalization program can be a reference for other watershed management toward environmental improvement using the same scheme. This study is expected to provide updated information on water quality in the downstream Citarum watershed several years after revitalization and provide an overview of the important functions of river revitalization